2018
DOI: 10.1016/j.archger.2018.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Self-care profiles of the elderly institutionalized in Elderly Care Centres

Abstract: The concept of self-care in the elderly has been frequently associated with autonomy, independence and personal accountability. Self-care practices are a result of individual lifestyles and paths adapted to the circumstances and expectations of the elderly. Based on the model by Backman and Hentinen (1999), the present study attempts to categorically describe the types of self-care of the elderly. This is an exploratory study, transversal, of a quantitative nature. The sample was comprised of 313 participants,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…The results obtained concerning the functional capacity in performing the BADL and the IADL regarding the selfcare profiles are consistent with the conceptualisation made by Backman and Hentinen for the typology of selfcare profiles (7). The results by others (20) further validate and add value to the research and to the present study, since our conclusions can be further supported by empirically derived data.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The results obtained concerning the functional capacity in performing the BADL and the IADL regarding the selfcare profiles are consistent with the conceptualisation made by Backman and Hentinen for the typology of selfcare profiles (7). The results by others (20) further validate and add value to the research and to the present study, since our conclusions can be further supported by empirically derived data.…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, the four clusters were created firstly by establishing the correct number of profiles using the latent profile analysis approach and afterwards by using the combination method of cluster analysis described by Hair et al and derived theoretically according to the model of Backman and Hentinen and Rasanen, Backman and Kyngas . Furthermore, a recent study which used the same sample, validated the self‐care profiles model, both statistically and theoretically.…”
Section: Methodsmentioning
confidence: 74%
“…Aging associated with changes in the new health condition does not impose a state of incapacity or dependence in the face of self-care actions, for the elderly. Thus, it is important to give due consideration to the social roles exercised, as well as performing self-care actions, allowing them to provide a state of well-being and autonomy [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Responsible and abandoned self-care profiles have a lower risk when compared with an independent profile. People with an independent self-care profile value autonomy and take unnecessary risks, which can result in falls [32, 41]. In fact, this profile has a higher chance of falling than the others.…”
Section: Discussionmentioning
confidence: 99%
“…The domains of the SCEF (walking, transferring, turning, lifting, using the toilet, feeding, getting ready, dressing, bathing, taking medication, and recreational activities) are structured according to the International Classification for Nursing Practice (ICNP, 2006) [39] and the items of each domain are based on the Nursing Outcomes Classification (NOC) [40]. The study of the instrument metric properties showed a high fidelity rate [32, 41]. Higher values are indicative of a higher level of Independence.…”
Section: Methodsmentioning
confidence: 99%